What motivates Chinese consumers to avoid information about the COVID-19 pandemic?: The perspective of the stimulus-organism-response model. Issue 1 (January 2021) - Song, Shijie; Yao, Xinlin; Wen, Nainan
Highlights: A research model based on S-O-R framework is proposed to examine the factors that influence health information avoidance intention during the COVID-19 pandemic. Information avoidance in the COVID-19 pandemic is determined by consumers' negative affect: sadness, anxiety, and cognitive dissonance. Information avoidance intention influences consumers' subsequent intentions of taking preventive behaviors during the COVID-19 pandemic. Consumer's negative affect is influenced by perceived threat and perceived information overload during the COVID-19 pandemic. Abstract: This study investigated consumers' information-avoidance behavior in the context of a public health emergency—the COVID-19 pandemic in China. Guided by the stimulus-organism-response paradigm, it proposes a model for exploring the effects of external stimuli (perceived threat and perceived information overload) related to COVID-19 on consumers' internal states (sadness, anxiety, and cognitive dissonance) and their subsequent behavioral intentions to avoid health information and engage in preventive behaviors. With a survey sample ( N  = 721), we empirically examined the proposed model and tested the hypotheses. The results indicate that sadness, anxiety, and cognitive dissonance, which were a result of perceived threat and perceived information overload, had heterogeneous effects on information avoidance. Anxiety and cognitive dissonance increased information avoidance intention, while sadness decreased information avoidance intention. Moreover, information avoidance predicted a reluctance on the part of consumers to engage in preventive behaviors during the COVID-19 pandemic. These findings not only contribute to the information behavior literature and extend the concept of information avoidance to a public health emergency context, but also yield practical insights for global pandemic control.